A flexible nanofiber membrane containing dendritic oxygen probe for visual monitoring pressure distribution - Wang, Ting; Cai, Shaoyong; Wu, Jianchang; Jiang, Chengwei; Xiao, Ziyu; Akram, Muhammad; Cao, Ge; Tian, Yanqing (Talanta, 2024)
Pressure-sensitive paints (PSP) enable non-intrusive visualization of surface pressure distribution on model surface which is important for aerodynamic studies. However, conventional PSP materials suffer from photobleaching and inadequate sensitivity. In this work, we rationally designed and synthesized novel dendritic oxygen probes (PT1 and PT2) by covalently grafting fluorinated dendrons onto platinum tetrakis(pentafluorophenyl)porphyrin (PT0) (a common oxygen probe). Subsequently, PT2 loaded nanofibers membranes from polycaprolactone (PCL) were fabricated by electrospinning. Fabricated membranes showed high oxygen sensitivity (I0/I100 = 35.3) with excellent flexibility, good reversibility, and outstanding photostability (merely 2.0% intensity loss after prolonged irradiation). The pressure sensitivity was found around 0.73 % per kilopascal. Furthermore, significant variation in emission intensity with respect to the variation in air pressure (1.3–101.32 kPa), facilitates the naked eye visualization of the pressure distribution on the membrane surface. Such excellent oxygen and pressure sensitivity and photostability might be due to high fluorine contents of complex dendritic structure of PT2. This flexible fluorine-functionalized dendritic oxygen probe puts forward a facile and effective strategy to develop advanced PSP materials enabling accurate pressure mapping for aerodynamic studies.
CRIS-Team Scopus Importer:2024-05-10
Keywords: Dendritic copolymer; Fluorine; Oxygen sensitivity; Platinum porphyrin; Pressure-sensitive paints